(3GdHjGf GdeZQH aj CNHGQ edhc GdeZQHs - (3eMeO GdeQGcTj, CHh YHO Gddg GdeYQha HGHf YPGQj,J (B695 (3g` s
(3ChdgG (B:s
(3GNJUGQ GdNHR HMQcI JGTajf Edi GdLHd dbJGd GdehMOjf s
(3BNQgG (B:s
(3jfJgi CKfGA CNHGQ SfI (B664 (3ai GdcdGe Yf MQcI GdhGKb HGddg EdG GdShS hBNQ GdehLhO efg hVQHJ GdWHhd ETYGQkG HGdEbHGd Ydjg aYeJ GdeSQGJ GdfahS LejYkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B95s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(200(3b(B) s
Keywords: (3GdJGQjNs